THU0143 Tofacitinib (CP-690, 550), an oral janus kinase inhibitor: Analyses of efficacy endpoints by subgroups in a pooled phase 2 and 3 rheumatoid arthritis study population. (23rd January 2014) - Kremer, J.; Zerbini, C.; Lee, E.B.; Gruben, D.; Krishnaswami, S.; Zwillich, S.H.; Koncz, T.; Bradley, J.; Mebus, C.A.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor investigated as a targeted immunomodulator for rheumatoid arthritis (RA). Objectives: This is an analysis of the populations pooled across Phase 2 and 3 RA studies to assess whether there is consistency in the treatment effect of tofacitinib in subgroups of patients. Methods: The demographic and baseline disease characteristics of patients in the Phase 2 and Phase 3 studies were similar, which supports the pooling of these data. Data from patients receiving tofacitinib 5 or 10 mg twice daily (BID) or placebo in all randomised Phase 2 and Phase 3 studies ≥3 months in duration (monotherapy studies NCT00550446, NCT00687193, and NCT00814307 ; background DMARD Studies NCT00413660, NCT00603512, NCT00960440, NCT00847613, NCT00856544, and NCT00853385 ) were pooled. ACR20 response rates and rates of improvement from baseline of at least 0.22 in the HAQ-DI at Month 3 were analysed by baseline demographics and disease characteristics and results were expressed as probability ratios (proportion of responders randomised to tofacitinib treatment(s) divided by that of placebo at Month 3) and 95% confidence intervals (CIs). Treatment comparisons included 5 mg BID, 10 mg BID, and 5 and 10 mg BID groups combined, vs placebo. Additionally, ACR20 response rates and change from baseline in the HAQ-DI at Month 3 were analysed by previous treatment experience (traditional DMARDs and TNF inhibitors). Results: In an analysis of 3442 patients in total, tofacitinib demonstrated consistent efficacy in reducing signs and symptoms of RA and improving physical function, as measured by ACR20 and HAQ-DI, respectively, compared to placebo. The probability ratios for all treatment comparisons for ACR20 and HAQ-DI responder rates were ≥1, with the lower boundary of the 95% CIs also ≥1 for all but one subgroup. Efficacy was seen in all subgroups evaluated including: age (18-44, 45-64, and ≥65 years); gender; weight (<60, 60-100, and >100 kg); body mass index (BMI, <18.5, 18.5 to <25, 25 to <30, and ≥30); race (white, black, Asian, other); region (USA, Latin America, Europe plus Canada, and rest of the world); RA duration (<2, 2 to <5, 5 to <10, and ≥10 years); serological status (RF or CCP +), and baseline DAS28-4 (ESR) (≤5.1 and >5.1). The black race group appeared to have lower response rates than the other race groups, although the CI for this group was wide and the sample size relatively small. Tofacitinib also demonstrated consistent efficacy in patients previously treated with traditional DMARDs or TNF inhibitors, irrespective of the number of previous treatments. Conclusions: Tofacitinib was consistently efficacious, as measured by ACR20 and HAQ-DI, across the range of baseline demographics and disease characteristics such as age, gender, weight, BMI, race, geographic region, disease duration, serological status, disease activity and previous treatment experience. Disclosure of Interest: J. Kremer Grant/Research support from: Pfizer Inc, Consultant for: Pfizer Inc, C. Zerbini: None Declared, E. B. Lee Consultant for: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Koncz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Mebus Shareholder of: Pfizer Inc, Employee of: Pfizer Inc